Condition monitoring through temperature, vibration and radio frequency emission - Alkahtani A.A.; Nordin F.H.; Sharrif Z.A.M.; Ramasamy A.K.; Norzeli S.M.; Alkharasani W.; Md Din N.; Tiong S.K.; Ekanayake J.B. (Mattingley Publishing, 2023)
Radio waves; Temperature; Vibration analysis; Electrical equipment; Intensive research; Monitoring methods; Performance and reliabilities; Radio frequency emissions; Reliable measurement; Three parameters; Unscheduled maintenance; Condition monitoring